Serological evidence of virus infection in Eidolon helvum fruit bats: implications for bushmeat consumption in Nigeria - Cantoni, Diego; Mayora-Neto, Martin; Derveni, Mariliza; da Costa, Kelly; Del Rosario, Joanne; Ameh, Veronica O.; Sabeta, Claude T.; Auld, Bethany; Hamlet, Arran; Jones, Ian M.; Wright, Edward; Scott, Simon D.; et al. (Frontiers in Public Health, 2023)
Introduction: The Eidolon helvum fruit bat is one of the most widely distributed fruit bats in Africa and known to be a reservoir for several pathogenic viruses that can cause disease in animals and humans. To assess the risk of zoonotic spillover, we conducted a serological survey of 304 serum samples from E. helvum bats that were captured for human consumption in Makurdi, Nigeria. Methods: Using pseudotyped viruses, we screened 304 serum samples for neutralising antibodies against viruses from the Coronaviridae, Filoviridae, Orthomyxoviridae and Paramyxoviridae families. Results: We report the presence of neutralising antibodies against henipavirus lineage GH-M74a virus (odds ratio 6.23; p<0.001), Nipah virus (odds ratio 4.04; p=0.00031), bat influenza H17N10 virus (odds ratio 7.25; p<0.001) and no significant association with Ebola virus (odds ratio 0.56; p=0.375) in this bat cohort. Conclusions: The data suggest a potential risk of zoonotic spillover including the possible circulation of highly pathogenic viruses in E. helvum populations. These findings highlight the importance of maintaining sero-surveillance of E. helvum, and the necessity for further, more comprehensive investigations to monitor changes in virus prevalence, distribution over time, and across different geographic locations.